Determination of some heavy metals from aqueous solutions using modified Amberlite XAD-4 resin by selective solid-phase extraction - Kocaoba, Sevgi (SPRINGER INT PUBL AG, 2022)
The adsorption efficiency of Pb(II) and Cd(II) from aqueous solutions on m-phenylenediamine-modified Amberlite XAD-4 resin was investigated. The effects of pH, adsorbent amount, initial metal concentration, eluent type and volume and flow rate on the retention of the metal ions have been studied on column studies. The optimum parameters were determined as pH 5, concentration 10 mg/L, stirring time 30 min and 0.2 g adsorbent amount and flow rate 2.5 mL/min for a quantitative adsorption. Sorption data were interpreted in terms of Langmuir and Freundlich equations, and both models were found to be fully appropriate. Each column can be used up to 10 sequential analyses without considerable change. The results indicate high metal adsorption capacity and satisfactory recovery of Pb(II) and Cd(II).
Keywords: Amberlite XAD-4 resin; Cd(II); Pb(II); Preconcentration; Solid-phase extraction; ABSORPTION SPECTROMETRIC DETERMINATION; WASTE-WATER TREATMENT; CHELATING RESIN; TRACE-METALS; ENVIRONMENTAL-SAMPLES; BIOLOGICAL SAMPLES; REMOVAL; IONS; COPPER; Chemistry